Novel polymorphic microsatellite DNA markers from Malaysian giant freshwater prawn, Macrobrachium rosenbergii. - See, Leng Min; Hassan, Rosly; Tan, Soon Guan; Bhassu, Subha (Springer, 2011)
Seven single locus microsatellite markers were characterized in Malaysian giant freshwater prawn, Macrobrachium rosenbergii from an enriched genomic library Primer pairs were designed to flank the repeat sequences and the loci characterized for this species. The bands resulting from the PCR amplifications of these eight microsatellite loci were polymorphic with the number of alleles ranging from 8 to 26 alleles per locus, whereas the observed heterozygosity ranged from 0.0641 to 0.6564. These newly developed microsatellite markers should prove to be useful for population studies and in the management of genetic variations in broodstocks of freshwater prawn, M. rosenbergii.